Design and Build of Automatic Hand Sanitizer Using Arduino - Budi Paul Sitompul; Solikhun Solikhun; Widodo Saputra; Indra Gunawan; Sumarno Sumarno (Green Publisher Indonesia, 2021)
An automatic handwashing deviceis a handwashing devicethat works automatically by utilizing an infrared sensor as a hand detector and using the Arduino Uno as the main controller. In this study, the authors discussed the design of an Automatic Handwashing Devicethat is placed on the hand-sanitizer faucet using the InfraRed sensor (detecting hand movements) based on Arduino Uno. This system includes the design of hardware (Hardware) and software (Software). Researchers use descriptive analysis techniques that are presented in table form. In this study, the authors conducted an analysis and design of the devices used to build the input and output processes including System Algorithms, Research Design, and Research Flowcharts. The results showed that the Hands Sanitizer deviceautomatically runs well and can be assembled using Arduino Uno microcontroller components and IR (Infrared) sensors. In making this program, the Arduino Uno application software is needed.